Plant tissues as a source of nutraceutical compounds: fruit seeds, leaves, flowers and steams - Velderrain Rodríguez, Gustavo (Apple Academic Press / CRC Press, 2018)
Plants have a huge role in human health and nutrition since ancient time, when man started to build sedentary societies. Man started to domesticate plants to use them as food, and eventually realized that some plant tissues had beneficial properties against diverse illness and problems they faced at the time. Nowadays, scientific research had exhaustively studied thousands of different plant tissues, from fruit seeds to flowers and stems. Scientific data now have identified that most of the chemical compounds in plants, also known as phytochemicals, involved in the color and texture of diverse plant tissues are responsible for many of the benefits that its consumption may bring to humans. In that sense, the diverse colors, shapes, and textures of plant tissues may be key points to consider at the time of looking for the right phytochemical to use in food products. The growing demand on economic and healthy food products leads the food industry to the exploitation and development of novel functional foods and nutraceutical products. In order that as the content of phytochemicals such as polyphenols, dietary fiber, carotenoids, free fatty acids, and vitamins in plant tissues may vary from one species to another, it is essential to analyze the common origin of each phytochemical compound from one plant tissue to another. Hence, this chapter summarizes the most common phytochemicals considered as nutraceutical compounds, its related health benefits, and the diverse plant tissues where we could find a specific type of phytochemical